Birsa Munda and his movement, 1874-1901 : a study of a millenarian movement in Chotanagpur - Singh, K. Suresh (Kumar Suresh), 1935- (Oxford, 1983)
Life and activities of Birsa Munda, 1874-1901, a leader in the peasant movement against the British policy on land distribution system in Bihar.